Biofertilizante de dejetos de suínos na fertilidade do solo e na produtividade de milho - Bócoli, Marcelo Eduardo (2014)
Organic materials submited to a process of anaerobic digestion, using a digester, produce biogas and biofertilizer which can be used in agriculture as a source of nutrients. The objective of this study was to evaluate the effect of biofertilizers swine manure in soil chemical properties, yield and nutrient content in leaves and grain of corn. The experiment was conducted under field conditions in IFSULDEMINAS - Campus Muzambinho - MG. Employed an experimental design of randomized blocks with 7 treatments and 4 replications, totaling 28 plots. The treatments consisted of biofertilizer doses of swine manure equivalent to doses 0, 40, 80, 120, 160, 200 and 240 m3 ha-1, applied once, 17 days after maize sowing. At 33 days after the application of biofertilizers were collected in each plot soil samples at 0-10, 10-20 and 20-40 cm depth. Harvest was performed 129 days after sowing of maize, having assessed the usable area of the plots grain yield, yield components (number of grains per ear, 1000 grain weight, size and diameter of the ears) and nutrient concentration in corn grain. The application of up to 240 m3 ha-1 of biofertilizers swine manure in soil with good fertility conditions did not alter the chemical soil properties and corn yield. The use of biofertilizers swine manure did not affect the levels of macronutrients and micronutrients in leaves and grains of corn.